DIGITAL PROFICIENCY STRENGTHENS SOCIAL PRESENCE IN ONLINE COURSES - Marques Junior, E.; Oliveira Neto, J. D.; Marques, E. M. R. [UNESP]; Chova, L. G.; Martinez, A. L.; Torres, I. C. (Iated-int Assoc Technology Education A& Development, 2014)
According to the Community of Inquiry (COI) framework, collaborative learning in distance learning courses promotes and sustains education as a social process, based on the sharing of educational resources and on a solidary construction of knowledge. A fundamental factor in the efficiency of collaborative apprenticeship is social interaction, which can be measured through social presence, the participant's ability to identify with the community, communicate with intent in a trusting environment, and develop relationships by projecting their personality. Given that distance learning supports itself with new technologies of information and communication, digital proficiency, which represents a student's capacity in this domain, can affect his or her social interaction. In spite of this, researches on social presence haven't been taking digital proficiency into consideration. This article's purpose is to examine digital proficiency's effect on the perception of social presence within collaborative learning environments. With this goal in mind, an analysis of the correlations between digital proficiency and social presence was undertaken from a sample of 76 online discussion forum participants, which included Brazilian college students and teachers. The results indicate a positive correlation (significant to a 0.01 level) between digital proficiency and social presence. This suggests that improving the digital proficiency of students will help to develop social presence perception. This perception enables students to benefit from more favorable conditions for interactions in the learning environment and improves computer-based collaborative learning.
Keywords: Digital proficiency; social presence; blended learning; computer-supported collaborative learning; Community of Inquiry